2016
DOI: 10.1007/s00253-016-7859-z
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of denitratating bacteria from a methylotrophic denitrifying culture

Abstract: Denitratation (nitrite produced from nitrate), has the potential applications in wastewater treatment by combining with ANAMMOX process. The occurrence of denitratation has been shown to be effected qualitatively by various parameters in the environment. A more quantitative understanding can be obtained using enrichment cultures in lab-scale experiments, yet information on the enrichment of functional microorganisms responsible for denitratation is lacking. In this study, a stable denitratation-dominated cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…), such as those resulting from fertilizer 2 and explosives manufacturing, 3,4 provide similar energy and chemical reduction opportunities through distinct short-cut BNR processes. A particularly effective pathway for treating waste streams containing both NH 4 + and NO 3 − is through heterotrophic [5][6][7][8][9][10] or autotrophic 11 denitratation (selective reduction of NO , such as those previously described, would theoretically reduce aeration energy requirements by 100% and COD requirements by 60% compared to treatment of the same waste stream using conventional BNR. 12 These benefits translate to municipal wastewater treatment as well, with a 50% decrease in aeration energy and 80% in COD requirements for a partial nitrification-denitratation-anammox system.…”
mentioning
confidence: 99%
“…), such as those resulting from fertilizer 2 and explosives manufacturing, 3,4 provide similar energy and chemical reduction opportunities through distinct short-cut BNR processes. A particularly effective pathway for treating waste streams containing both NH 4 + and NO 3 − is through heterotrophic [5][6][7][8][9][10] or autotrophic 11 denitratation (selective reduction of NO , such as those previously described, would theoretically reduce aeration energy requirements by 100% and COD requirements by 60% compared to treatment of the same waste stream using conventional BNR. 12 These benefits translate to municipal wastewater treatment as well, with a 50% decrease in aeration energy and 80% in COD requirements for a partial nitrification-denitratation-anammox system.…”
mentioning
confidence: 99%
“…organic carbon, ferrous iron (Fe 2+ ), or sulfide (S 2− )] to NO 3 − reduction that if completely reduced, eventually forms nitrogen gas (Lu et al 2014). Recent work has confirmed that organic carbon compounds such as methanol and acetate favor specific denitrifying bacteria and successfully removes NO 3 − (Li et al 2016a). However, the use of methanol as an electron donor produces CaCO 3 , which increases the pH, and affects the denitrifying microbial community in the system.…”
Section: Introductionmentioning
confidence: 94%
“…DNA concentration and purity were determined with microspectrophotometry (NanoDrop ® ). Extracted DNA was sent to Mingke Biotechnology (Hangzhou) Co., Ltd, amplified with 341F (5′-CCTAYGGGRBGCASCAG-3′) and 806R (5′-GGACTACNNGGGTATCTAAT-3′) [22,23]. The purified amplicons were then sequenced on an Illumina Miseq sequencing platform.…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%